Validity and Reliability of Satisfaction as a Mediator between Quality Constructs in Manufacturer–Supplier Relationships Through Time and Across Contexts. Issue 1 (2nd January 2017) - Padin, Carmen; Ferro, Carlos; Svensson, Göran
Abstract: Purpose : The main objective is to test and assess a research model through time and across contexts in which satisfaction is a mediator between quality constructs in manufacturer–supplier relationships. Satisfaction is positioned as a mediator between trust and commitment (i.e., causes) on the one hand, and cooperation, coordination and continuity expectancy (i.e., outcomes) on the other. The objective is also to provide a substantiation and contribution through time and across contexts, to business theory of supplier-manufacturer relationships Methodology/approach : One out of eight samples selected for additional empirical substantiation for this study comprises a total of 600 small and medium-sized Spanish enterprises from various industrial sectors. A total of 259 usable questionnaires were returned, generating a response rate of 43.2%. The study is positioned (and compared) in relation to seven other samples that have been tested within the same research model in Canada, Finland, Norway (twice), South Africa, Sweden, and Taiwan. The total number of useable questionnaires is 1641, the average number of useable questionnaires per study is 205 and the average response rate is 37.4% in the studies assessed of this article. Findings : The research model tested and assessed in the eight studies meets the requirements for satisfactory convergent, discriminant and nomological validity, as well as for construct reliability. The measurement and structural metrics support validity and reliability over time and across contexts, which is rare in marketing research. Research implications : The theoretical framework contributes, through time and across contexts, to the business theory of supplier–manufacturer relationships. The tested research model demonstrates properties of validity and reliability across countries and company sizes. Implications and suggestions for further research are provided. Practical implications : The empirical findings indicate key factors that contribute to satisfaction in manufacturer–supplier relationships in different countries and companies. Originality/value : The article makes a contribution to theory relating to supplier–manufacturer relationships, providing evidence that the tested, hypothesized relationships are generally applicable. The validation or falsification of empirical findings in previous research is crucial in building valid and reliable theory over time and across contexts. Otherwise, theory becomes fragmented and undermines the credibility of marketing research.